Assessment of Tourist Competitiveness by analysing Destination Efficiency - Francesca Cracolici; Piet Rietveld; Peter Nijkamp (Tinbergen Institute, 2006)
Recently the notion and the measurement of destination competitiveness have received increasing attention in the economics literature on tourism. The reason for this interest emerges from both the increasing economic importance of the tourist sector and the increasing competition on the tourist market as a consequence of the transition from mass tourism to a new age of tourism that calls for a tailor-made approach to the specific attitudes and needs of tourists. The central subject of this paper – inspired by the conceptual competitiveness model developed earlier by Crouch and Ritchie – concerns the efficiency of tourist site destinations. Using a dataset of 103 Italian regions for the year 2001, an economic efficiency analysis based on a production frontier approach has been made in the present study. The study deploys a measure of tourist site competitiveness in terms of its technical efficiency using parametric and non-parametric methods, a stochastic production function and data envelopment analysis, respectively.
Keywords: L83; 330; competitiveness; Italian tourist industry; envelopment analysis